Gene hydrogel platforms for targeted skin therapy: bridging hereditary disorders, chronic wounds, and immune related skin diseases - Li, Liangtao (Frontiers in Drug Delivery, 2025)
Gene therapy, a pivotal cornerstone in biomedical research, has emerged as a transformative approach for addressing a wide spectrum of dermatologic conditions, including hereditary disorders, chronic wounds, and immune related skin diseases. The skin, with its expansive surface area and regenerative capacity, serves as an ideal platform for localized gene delivery. However, conventional gene therapy strategies face critical limitations, such as high costs, suboptimal transfection efficiency, immunogenicity, and off-target effects. In this context, gene hydrogels have emerged as an innovative paradigm, offering tailored physicochemical and biological functionalities to overcome these challenges. Gene hydrogels are distinguished by their tunable morphologies (e.g., particulate or bulk gel configurations), which enable precise control over therapeutic release kinetics and spatial distribution. Their three-dimensional polymeric networks recapitulate the extracellular matrix, functioning as bioactive scaffolds that enhance tissue regeneration, facilitate cell migration, and accelerate wound healing. By integrating stimuli-responsive polymers, these hydrogels achieve spatiotemporal control of gene delivery, improving target specificity while minimizing systemic exposure. Furthermore, their inherent biocompatibility and biodegradability mitigate immunogenic risks and prevent long-term residue accumulation, addressing pivotal safety concerns in clinical translation. This review systematically examines the multifaceted advantages of gene hydrogels, including their ability to bypass the stratum corneum barrier, protect genetic payloads from enzymatic degradation, and sustain localized therapeutic effects over extended periods. Recent advancements in “smart” hydrogels, responsive to pathological cues such as pH fluctuations or matrix metalloproteinase overexpression, further underscore their potential in personalized medicine. By synergizing material science with gene-editing technologies, gene hydrogels represent a revolutionary leap toward precision dermatologic therapies. Future challenges, such as scalable manufacturing and dynamic regulatory mechanisms, are critically analyzed alongside opportunities in intelligent material design and interdisciplinary innovation. This comprehensive analysis positions gene hydrogels as a cornerstone for next-generation dermatologic therapeutics, bridging the gap between laboratory innovation and clinical impact.